Desert loess: a selection of relevant topics - Smalley, Ian; Marshall, John; Fitzsimmons, Kathryn; Whalley, W. Brian; Ngambi, Samson (Geologos, 2019)
In discussions on loess, two types are often demarcated: glacial loess and desert loess. The origin of the idea of desert loess appears to lie with V.A. Obruchev who observed wind-carried silt on the Potanin expedition to Central Asia in 1895. It might be considered that desert loess would be defined as loess associated with deserts but it came to be thought of as loess produced in deserts. This led to some controversy as no mechanism for producing silt particles in deserts was readily available. Bruce Butler in Australia in particular cast doubt on the existence of desert-made loess. Butler indicated loess-like deposits in Australia which he called Parna; these are very like loess but the silt sized particles are actually clay mineral agglomerates of silt size- formed in dry lake regions. At the heart of the desert loess discussion is the problem of producing loess material in deserts. It has been suggested that there are no realistic mechanisms for forming large amounts of loess dust but there is a possibility that sand grain impact may produce particle shattering and lead to the formation of quartz silt. This would appear to be a reasonable mechanism for the African deposits of desert loess, but possibly inadequate for the huge deposits in China and Central Asia. The desert loess in China and Central Asia is loess associated with a desert. The material is formed in cold, high country and carried by rivers to the vicinity of deserts. It progresses then from deserts to loess deposit. Adobe ground may be defined as desert loess. Adobe occurs on the fringe of deserts, notably in the Sahelian region of Africa, and in SW USA. The use of adobe in construction represents the major utilization of desert loess in a social context. More understanding of adobe is required, in particular with respect to the adobe reaction, the low order chemical reaction which provides modest cementitious properties, and can be likened to the pozzolanic reactions in hydrating cement systems. The location of loess and loess-like ground on the peripheries of deserts is aided by the observation of the nesting sites of bee-eater birds. These birds have a determined preference for loess ground to dig their nesting tunnels; the presence of nest tunnels suggests the occurrence of desert loess, in desert fringe regions. We seek amalgamation and contrast: ten main topics are considered: words and terms, particles, parna, geotechnical, adobe, people, birds, Africa, Central Asia, Mars. The aim is some large generalizations which will benefit all aspects of desert loess investigation.